Establishment of flow stress model and optimization of process parameters for ZK10 magnesium alloy with low zinc-content during isothermal compression - Zhang, Yu; Bao, Jiaxin; Duan, Wenchao; Yin, Siqi; Cui, Jianzhong; Zhang, Zhiqiang (Journal of materials research and technology, 2021)
Under the condition of strain rates of 0.001–1 s−1 and temperatures of 473–723 K, the flow behaviors of the cast-homogenized ZK10 magnesium alloy were studied through the isothermal compression test with final true strain of 1. In view of this, the Arrhenius equation subject to strain was treated with a comprehensive correction, the deformation activation energy Q of ZK10 alloy was calculated to be 181.87 kJ/mol, and a reliable flow stress model of ZK10 alloy was established. Meanwhile, the processing maps and microstructure evolution of ZK10 alloy were analyzed, which indicated that obvious dynamic recrystallization occurred during thermal compression deformation of ZK10 alloy under the above process conditions. When ZK10 alloy was hot compressed at 473 K in the instability zone, serious instability deformation and macro cracks occurred at strain rates of 0.001 s−1 and 0.01 s−1. The optimum process parameter of ZK10 alloy under the experimental conditions was obtained to be 673 K/1 s−1, and the corresponding microstructure was the most uniform and finest, which provides useful guidance for the selection of process parameters of ZK10 alloy.